The viral protein R in HIV-associated acute ischaemic stroke: a case-control study - McMullen, Kate (Department of Medicine, 2022)
Background: HIV-1 viral proteins have been implicated in endothelial dysfunction, which is a major determinant of ischaemic stroke risk in HIV-infected individuals. Polymorphisms in HIV-1 viral protein R (Vpr) may alter its potential to promote endothelial dysfunction, by modifying its effects on viral replication, reactivation of latent cells, upregulation of proinflammatory cytokines and infection of macrophages. Methods: We analysed Vpr polymorphisms and their association with acute ischaemic stroke by comparing Vpr signature amino acids between 54 HIV-infected individuals with acute ischaemic stroke, and 80 age-matched HIV-infected non-stroke controls. Results: Isoleucine at position 22 and serine at position 41 were associated with ischaemic stroke in HIV. Individuals with stroke had lower CD4 counts and CD4 nadirs than controls. These polymorphisms are more common in individuals with stroke compared to South African subtype C and the control group consensus sequences. Conclusions: Signature Vpr polymorphisms have been identified that are more common in people with acute ischaemic stroke in HIV compared to HIV-infected individuals without acute ischaemic stroke. These may be involved in increased stroke risk by promoting endothelial dysfunction and susceptibility to opportunistic infections, as well as more advanced HIV disease. Therapeutic targeting of HIV-1 viral proteins may present an additional mechanism of decreasing stroke risk in HIV-infected individuals.